2023
DOI: 10.3389/fpls.2023.1139526
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide identification and expression analysis of the HVA22 gene family in cotton and functional analysis of GhHVA22E1D in drought and salt tolerance

Abstract: The HVA22 family of genes, induced by abscisic acid and stress, encodes a class of stress response proteins with a conserved TB2/DP1/HVA22 domain that are unique among eukaryotes. Previous studies have shown that HVA22s play an important role in plant responses to abiotic stresses. In the present study, 34, 32, 16, and 17 HVA22s were identified in G. barbadense, G. hirsutum, G. arboreum, and G. raimondii, respectively. These HVA22 genes were classified into nine subgroups, randomly distributed on the chromosom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 66 publications
1
8
0
Order By: Relevance
“…In comparison, six genes were identified in the D genome of G. hirsutum. Tetraploid cotton is an allotetraploid formed by hybridizing diploids with At and Dt genomes [ 32 ].The number of CSP genes in tetraploid cotton ( G. hirsutum , G. barbadense ) was nearly twice that of diploid cotton ( G. arboreum , G. raimondii ), indicating that the CSP family is conserved throughout evolution. These results indicate that the number of CSPs varies slightly across different cotton species, potentially due to the loss or duplication of genes over the course of cotton evolution.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In comparison, six genes were identified in the D genome of G. hirsutum. Tetraploid cotton is an allotetraploid formed by hybridizing diploids with At and Dt genomes [ 32 ].The number of CSP genes in tetraploid cotton ( G. hirsutum , G. barbadense ) was nearly twice that of diploid cotton ( G. arboreum , G. raimondii ), indicating that the CSP family is conserved throughout evolution. These results indicate that the number of CSPs varies slightly across different cotton species, potentially due to the loss or duplication of genes over the course of cotton evolution.…”
Section: Resultsmentioning
confidence: 99%
“…Contemporary studies have indicated that CSP activity in plants is influenced by various abiotic stress factors, and the examination of gene expression patterns is often employed to characterize gene function [ 32 ]. Via analysis of expression patterns before and after stress, it was determined that the expression of four genes ( GhCSP.A1 , GhCSP.A2 , GhCSP.A3 , and GhCSP.A7 ) was upregulated under low temperatures.…”
Section: Discussionmentioning
confidence: 99%
“…Most unassigned genes (20) had some form of annotation that could be inferred from the gene family. Of which, orthologs of Mp1g15330.1 (HVA22-like, Zhang et al ., 2023), Mp5g01770.1 (temperature-induced lipocalin, Abo-Ogiala et al ., 2014) and Mp5g15480.1 (interferon-related developmental regulator family protein, Park et al ., 2009) have been implicated in stress response.…”
Section: Resultsmentioning
confidence: 99%
“…In barley vegetative tissues, the expression of HVA22 was also shown to be induced by ABA, cold and drought. Since then, diverse abiotic stresses such as temperature, salinity and drought have been shown to differentially regulate the expression of HVA22 homologues in various plant species (Courtney et al., 2016 ; Gomes Ferreira et al., 2019 ; Lyu et al., 2021 ; Wai et al., 2022 ; Zhang, Wen, et al., 2023 ; Zhang, Yuan, et al., 2023 ). However, only a limited number of studies describe the function of those HVA22 genes in plants.…”
Section: Discussionmentioning
confidence: 99%
“…In Arabidopsis , reticulon proteins (called RTNLB) have also been described (Nziengui et al., 2007 ). The overexpression of a number of RTNLBs in tobacco leaf epidermal cells is sufficient to constrict the ER lumen and convert ER sheets into tubules (Sparkes et al., 2010 ; Tolley et al., 2008 ; Zhang, Wen, et al., 2023 ; Zhang, Yuan, et al., 2023 ), suggesting a conserved role for these proteins in eukaryotes. The membrane curvature is induced by two long hydrophobic regions displaying a wedge‐like topology (Wang et al., 2021 ).…”
Section: Discussionmentioning
confidence: 99%